Snail2 controls mesodermal BMP/Wnt induction of neural crest - Shi, Jianli (Company of Biologists, 2011)
The neural crest is an induced tissue that is unique to vertebrates. In the clawed frog Xenopus laevis, neural crest induction depends on signals secreted from the prospective dorsolateral mesodermal zone during gastrulation. The transcription factors Snail2 (Slug), Snail1 and Twist1 are expressed in this region. It is known that Snail2 and Twist1 are required for both mesoderm formation and neural crest induction. Using targeted blastomere injection, morpholino-based loss of function and explant studies, we show that: (1) Snail1 is also required for mesoderm and neural crest formation; (2) loss of snail1, snail2 or twist1 function in the C2/C3 lineage of 32-cell embryos blocks mesoderm formation, but neural crest is lost only in the case of snail2 loss of function; (3) snail2 mutant loss of neural crest involves mesoderm-derived secreted factors and can be rescued synergistically by bmp4 and wnt8 RNAs; and (4) loss of snail2 activity leads to changes in the RNA levels of a number of BMP and Wnt agonists and antagonists. Taken together, these results identify Snail2 as a key regulator of the signals involved in mesodermal induction of neural crest.